Non-linear FEM analysis of seismic induced pounding between neighbouring multi-storey structures - Jameel, Mohammed; Islam, A.B.M.; Hussain, Raja Rizwan; Hasan, Syed Danish; Khaleel, M. (2013)
Pounding of neighbouring construction of structures due to seismic excitation increases the damage of structural components or even causes collapse of structures. Among the possible building damages, earthquake induced pounding has been commonly observed in several earthquakes. Therefore it is imperative to consider pounding effect for structures. This study aims to understand the response behaviour of adjacent buildings with dissimilar heights under earthquake induced pounding. Effects of different separation distances between structures are also investigated. Nonlinear finite element analysis in time domain has been carried out for pounding of neighbouring structures having varying heights. To show the importance of avoiding pounding in structures the results obtained were compared with model having no pounding phenomena. The results were obtained in the form of storey shear, pounding force, storey drift, point displacement and acceleration. The acceleration at pounding level significantly increases during collision of building. The generated extra pounding force may cause severe damage to structural members of structures. Pounding produces shear at various story levels, which are greater than those obtained from no pounding case. Building with more height suffers greater damage than shorter building when pounding occurs. Increasing gap distance tends to reduce story shear in consistent manner. The results also show that the conventional modelling of building considering only beams and columns underestimates pounding effects. More realistic modelling such as beams, columns and slabs shall be adopted to accurately understand the pounding phenomenon.